2017
DOI: 10.1094/pdis-04-17-0477-re
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of a Web-Based Disease Forecast System for Control of Anthracnose and Botrytis Fruit Rots of Strawberry in Southeastern United States

Abstract: Strawberry production in Florida and South Carolina is affected by two major diseases, anthracnose fruit rot (AFR) and Botrytis fruit rot (BFR), caused by Colletotrichum acutatum and Botrytis cinerea, respectively. The effective management of both diseases traditionally relied on weekly fungicide applications. However, to improve timing and reduce the number of fungicide sprays, many growers follow the Strawberry Advisory System (StAS), a decision support system for forecasting fungicide applications based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…Meta-analysis was originally developed for analysis in the social sciences and medical sciences and recently has been adopted in plant pathology to examine results from many studies in a single, yet statistically powerful, analysis [ 22 ]. For example, meta-analysis was recently used in strawberry production to test the utility of using a disease warning system for advising fungicide applications versus using a calendar-based approach in applying fungicide for various fruit rots [ 24 ]. Similar techniques could be useful in calculating the probability of success in using a disease warning system over many site-years in turfgrass.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis was originally developed for analysis in the social sciences and medical sciences and recently has been adopted in plant pathology to examine results from many studies in a single, yet statistically powerful, analysis [ 22 ]. For example, meta-analysis was recently used in strawberry production to test the utility of using a disease warning system for advising fungicide applications versus using a calendar-based approach in applying fungicide for various fruit rots [ 24 ]. Similar techniques could be useful in calculating the probability of success in using a disease warning system over many site-years in turfgrass.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the experiment was conducted without cover, the wind and insects had free reign throughout the cycle. Regarding fruits with rot, the genotypes with the highest production of fruits in this category are possibly more susceptible to the fungi Botrytis cinerea and Colletotrichum acutatum, important causal agents of fruit rot in strawberry crops (CORDOVA et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Disease forecasting models help predict disease risks and reduce fungicide application by 50%. The anthracnose advisory system based on the AFR model showed that it could significantly reduce the number of sprayings [23,38]. Rasiukevičiūtė et al [22] evaluated the iMETOS ® strawberry Botrytis cinerea forecasting model.…”
Section: Discussionmentioning
confidence: 99%